Suberin-based polyurethanes: Synthesis, characterization and kinetics of their formation (BIOMASS FOR ENERGY AND INDUSTRY, 1998)
The synthesis and characterization of novel family of polyurethanes prepared by the polycondensation of suberin from Quercus suber L. with aliphatic and aromatic isocyanates are reported. A preliminary kinetic study, conducted with the aim of establishing the reactivity of suberin with different mono-, di- and polyisocyanates, showed that the kinetics of these condensations followed the classical second-order behaviour up to conversion of about 90%. The reactivity of different isocyanates followed patterns that could be readily rationalized in terms of steric hindrance and electronic factors, associated with each specific structure. The investigation was then extended to the synthesis of the new polymers which were characterized by FTIR and NMR spectroscopy and DSC. These suberin-based polyurethanes were a mixture of linear, branched and crosslinked structures. The proportion of the latter (insoluble fraction) being the highest for thr syntheses carried out in stoichiometric conditions, viz. \{[\}NCO](o) = \{[\}OH](o). The Tg of these materials depended of the diisocyanates used and correlated with their structural stiffness.